Clinical and laboratory observation systemic lupus erythematosus and acute lymphocytic leukemia: An unusual case - Anu Maheshwari; Meenu Pandey; Bimbadhar Rath; Jagdish Chandra; Smita Singh; Sunita Sharma (Indian Journal of Medical and Paediatric Oncology)
The association of systemic lupus erythematosus (SLE) and myeloproliferative and lymphoproliferative malignancies is widely reported. There is scarce information available with regards to the association of SLE and malignancy in children. Usually, SLE precedes the onset of lymphoproliferative disease, but the neoplasia can occur earlier or even simultaneously. There are only five pediatric cases of SLE and associated acute lymphoblastic leukemia (ALL) reported in literature. All of these except one satisfied the revised American College of Rheumatology Criteria for SLE. Three of these cases developed SLE several years after successful treatment of ALL. While two cases reported had simultaneous onset of SLE and ALL, one of the cases in this two-patient series, did not fulfill ≥4 criteria for diagnosis of SLE. We present a case of a 3-year-old boy with SLE and coexistent ALL. To the best of our knowledge, only two such cases of simultaneous presentation of both these diseases are present in literature.